2019
DOI: 10.1111/weng.12427
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual advertising in the linguistic landscape of Seoul

Abstract: This study examines commercial signs in arguably the two most visited tourism districts in Seoul, namely Myeongdong and Insadong. It focuses on beauty and food businesses and analyzes featured languages and their content and roles in signage. This article argues that business types, specialized marketing focus, and intended sales pitch influence business owners’ linguistic choices. The findings of the study suggest that the beauty industry relies heavily on English in general, but the power of K‐Beauty popular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…Our findings support previous research highlighting how English and coffee shops are sites of modernity and Western consumption (Lee, 2006;Tan & Tan, 2015). Additionally, we found, like Lee (2019), that Korean can be part of constructing a coffee shop as comfortable and nostalgic, as demonstrated by Seongsudong Coffee. However, our findings also push back against recent work on Korea's linguistic landscape.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings support previous research highlighting how English and coffee shops are sites of modernity and Western consumption (Lee, 2006;Tan & Tan, 2015). Additionally, we found, like Lee (2019), that Korean can be part of constructing a coffee shop as comfortable and nostalgic, as demonstrated by Seongsudong Coffee. However, our findings also push back against recent work on Korea's linguistic landscape.…”
Section: Discussionsupporting
confidence: 91%
“…A limited number of studies have examined the role of English in Korea's linguistic landscape (e. g. Vlack, 2011, Lawrence, 2012Park & Yang, 2015;Tan & Tan, 2015;Lee, 2019;Choi, Tatar & Kim, 2019). Importantly, Tan and Tan (2015: 66) found that English is often used in the brand names of products and stores and serves a decorative function in popular commercial areas, including those not frequented by tourists.…”
Section: English and Coffee In Korea And The Korean Linguistic Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…For example, it can be used both to convey information and to entice customers through the associations they make with English. In their work on English advertising, Tan and Tan (2015: 75–76) suggest that English functions as a status marker and view the use of English as “symbolic rather than information-giving in nature” (as cited in Lee, 2019: 501).…”
Section: The Functions Of Languagementioning
confidence: 99%
“…The salient presence of English in the linguistic landscape of the Outer and Expanding Circle countries mainly because of the visual appeal of its foreignness (Backhaus, 2019) is not unheard of, and its extensive use in the Korean linguistic landscape has been reported in numerous studies (e.g., Lawrence, 2012; Lee, 2019; McPhail, 2018). However, perceptions of the Korean public vis-à-vis this practice have rarely been explored thus far despite scholarly observations that nationalistic language attitudes in Korea are just as prominent as the heated pursuit of English (J. S.–Y.…”
Section: Introductionmentioning
confidence: 99%